Lentils pasta by-product in a complete extruded diet for dogs and its effect on extrusion, digestibility, and carbohydrate metabolism - Penazzi, Livio; Freire, Ticiane Giselle Bitencourt; Theodoro, Stephanie de Souza; Frias, Juliana Lopes; Ala, Ugo; Carciofi, Aulus Cavalieri; Prola, Liviana (Frontiers in Veterinary Science, 2024)
Recently, increasing effort has been directed towards environmental sustainability in pet food. The aim of this study was to evaluate the extrusion parameters, nutrient digestibility, faecal characteristics, palatability and insulinemic and glycaemic curves of a complete diet for dogs in which the main carbohydrate source was a red lentil pasta by-product (LP). Five experimental diets were formulated: a basal diet (CO) based on rice and a poultry by-product meal; three experimental diets where LP substituted rice at 33, 66 or 100% (LP33, LP66 and LP100, respectively); and a diet formulated on 70% of the basal diet (CO) plus 30% LP (LPS) to evaluate the digestibility of LP ingredient. The extruder pressure, hardness and bulk density of the kibble increased in a linear manner with increasing LP percentage (P < 0.05), without affecting starch gelatinization. According to polynomial contrast analysis, rice replacement with LP at 33 and 66% caused no reduction in apparent total tract digestibility coefficient (ATTDC), with similar or higher values compared with the CO diet. Nitrogen balance did not change (P>0.05), but we observed a linear increase in faeces production and moisture content as the LP inclusion rate rose and a linear decrease in faeces pH (P<0.05). Nevertheless, the faecal score was unaffected. Faecal acetate, propionate, total short-chain fatty acids (SCFA), branched-chain fatty acids, and lactate all increased linearly as the LP inclusion rate increased (P<0.05), without altering ammonia concentration in faeces. Faeces concentrations of cadaverine, tyramine, histamine and spermidine also increased in a linear manner with increasing LP inclusion (P<0.05). The fermentation of LP dietary fibre by the gut microbiota increased the concentration of desirable fermentation by-products, including SCFA and spermidine. The postprandial glucose and insulin responses were lower in the dogs fed the LP100 diet compared with CO, suggesting the possible use of this ingredient in diets designed to generate a low glycaemic response. Finally, the palatability study results showed a preference for the LP100 ration in both the "first choice" and the "consumption rate" evaluation (P<0.05). This trial reveals how a by-product discarded from the human-grade food chain retains both its nutritional and organoleptic properties.